Mathematics knowledge for teaching at the secondary levels: methods and evidence from the TEDS-M Study - Tatto, María Teresa (Universidad de Costa Rica, 2016)
This presentation describes the results of the Teacher Education and Development Study in Mathematics (TEDS-M) a collaborative study of the mathematics preparation of future primary and secondary teachers. The study explored the question of whether what future teachers learn in pre-service teacher education leads to more effective knowledge of mathematics and mathematics for teaching. The methods and results of TEDSM are examined in light of their contribution to a prospective international study of novice mathematics teachers known as The First Five Years of Mathematics Teaching or FIRSTMATH.